2022
DOI: 10.1039/d2bm00572g
|View full text |Cite
|
Sign up to set email alerts
|

Scar prevention through topical delivery of gelatin-tyramine-siSPARC nanoplex loaded in dissolvable hyaluronic acid microneedle patch across skin barrier

Abstract: Dissolvable microneedle patch made of HA designed for delivery of siSPARC across skin barrier to prevent scar formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Microneedles (MNs) represent a novel technology for drug delivery. [6][7][8] With micrometer-scaled needles arranged in a designed patch, the microneedle patch system has advantages such as minimal invasion and personalized and precise drug release and has attracted emerging attention in biosensing, 9,10 diagnosis, 11 and treatments of different diseases including diabetes, [12][13][14] cancers, 15,16 wounds, [17][18][19] scars, [20][21][22] and psoriasis. 23 The stratum corneum is the main barrier of the skin and limits the efficiency of transdermal drug penetration.…”
Section: Introductionmentioning
confidence: 99%
“…Microneedles (MNs) represent a novel technology for drug delivery. [6][7][8] With micrometer-scaled needles arranged in a designed patch, the microneedle patch system has advantages such as minimal invasion and personalized and precise drug release and has attracted emerging attention in biosensing, 9,10 diagnosis, 11 and treatments of different diseases including diabetes, [12][13][14] cancers, 15,16 wounds, [17][18][19] scars, [20][21][22] and psoriasis. 23 The stratum corneum is the main barrier of the skin and limits the efficiency of transdermal drug penetration.…”
Section: Introductionmentioning
confidence: 99%
“…However, a reduced collagen content was found in healing wounds of SPARC-knockout mice, leading to improved contractibility of wound edges and enhanced wound closure ( Bradshaw et al, 2002 ). In accordance with this finding, the downregulation of SPARC in mouse wounds led to delayed wound contraction and reduced collagen deposition, thus potentially preventing excessive scar formation ( Chun et al, 2022 ).…”
Section: Functions Of Matricellular Proteins In Cutaneous Wound Healingmentioning
confidence: 57%
“…Recent studies have shown that MNs can painlessly puncture the epidermis to form microscopic pores which facilitate the rapid diffusion of biologically active substances (drugs, cells, growth factors, genes, etc.) to the wound bed [ 43 , 46 , [104] , [105] , [106] ]. Table 1 summarizes representative recent studies of MNs for skin tissue regeneration.…”
Section: Mns For Istrmentioning
confidence: 99%